Facts and artefacts : art in the Islamic world : festschrift for Jens Kröger on his 65th birthday - Hagedorn, Annette.; Kröger, Jens.; Shalem, Avinoam. (Islamic History and Civilization, 2007)
The scholarly search on the art of the object is of enduring interest and enjoys a new renaissance in the last few years. This book mainly explores the art and craft of Islamic artefacts and presents to the reader a diverse range of approaches. Despite this variety, in which also artefacts of the pre-Islamic, period as well as 'orientalized' European artefacts of the modern era are included, there is an overarching theme - the linking of the interpretation of objects and their specific aesthetics to textual sources and the aim of setting them in historical and artistic context. In this impressive collection honouring the German scholar of Islamic art Jens Kröger on his 65th birthday, Avinoam Shalem and Annette Hagedorn bring together contributions from a highly distinguished group of scholars of Asiatic, Sasanian, Islamic as well as European art history. Unpublished artefacts and new interpretations are presented in this book.